Theoretical Study of the Effect of Thermal Stress on Transversal Damage of Hybrid Biocomposite Materials Flax-hemp/Polyethylene - Mokaddem, Allel; Doumi, Bendouma; Belkheir, Mohammed; Boutaous, Ahmed; Temimi, Elhouari (Current Materials Science, 2021)
Background: The objective of sustainable development in the field of materials necessitates and demands the substitution of the basic constituents of a composite material (carbon, glass, etc.) by natural reinforcements, which have a very important role in the protection of the environment and to subsequently have new materials with good properties compared to socalled traditional materials. Objective: In this context, we have investigated using genetic modeling based on probabilistic models the effect of thermal stress on transversal damage of a bio-composite hybrid Flax- Hemp/PE material. Methods: Our model genetic is based on probabilistic models of Weibull and the different values of the thermal stress were calculated by the Lebrun equation. To validate our theoretical calculations, we used the nonlinear parameter β in the Hoock law of the nonlinear acoustic technique to trace the curves of the damage under the mechanical and thermal stress. Results: The results obtained with a genetic simulation are in good agreement with the results found by Clément Gourier and Raphaël Kueny, who have shown that flax and hemp fibers (bark/Liberian fibers) are good reinforcements of the Polyethylene matrix; we found also found that our hybrid biocomposite material Flax-Hemp/PE is resistant in particular, a part of this material is of plant origin and gives us environmental benefit. Conclusion: It should be noted that the results obtained by the genetic simulation are in good agreement with the results obtained by the nonlinear acoustic technique mentioned by the green curve in all the figures. In perspective, it would be interesting to see, later, the effect of humidity on the damage of the matrix fiber interface of a hybrid biocomposite.
Keywords: hemp